One-Carbon Metabolites, B Vitamin Intake, Apolipoprotein E Genotype, and Their Interactive Effects on Cognitive Performance: Secondary Outcomes of the REACH Cohort. (7th June 2021) - Gillies, Nicola; Milan, Amber; Cameron-Smith, David; Conlon, Cathryn; von Hurst, Pamela; Haskell-Ramsay, Crystal; Jones, Beatrix; Mumme, Karen; Roy, Nicole; Coad, Jane; Wall, Clare; Beck, Kathryn
Abstract: Objectives: To investigate associations between one-carbon metabolites and cognitive performance in older adults, and to examine the interactive effects of B vitamin intake, apolipoprotein E genotype, and one-carbon metabolites on cognition. Methods: Three hundred and thirteen healthy older men and women (65–74 years, 65% female) were included in this secondary analysis of the REACH cohort. Cognitive performance was assessed by the Computerised Mental Performance Assessment System (COMPASS). Fasting plasma one-carbon metabolites (betaine, choline, cysteine, dimethylglycine, glycine, homocysteine, methionine, S -adenosylmethionine, serine) were quantified by ultra high performance liquid chromatography with tandem mass spectrometry, and four-day food records were analyzed for nutrient intake. Presence of the apolipoprotein E ε4 allele was measured by polymerase chain reaction amplification. Linear regression models were adjusted for age, sex, batch effects, education level, physical activity, energy intake and supplement use. Interaction terms were fit between continuous (metabolites) and categorical (quartiles of B vitamin intake or metabolites not fit as the main independent variable, presence of apolipoprotein ε4 allele) variables. Results: Higher glycine concentrations were associated with better global cognitive performance (β = 1.340, P  = 0.017), episodic memory (β = 1.396, P  = 0.016) and location learning (β = 1.394, P  = 0.027) in linear regression models, although this relationship was not apparent in participants with higher choline concentrations or the apolipoprotein ε4 genotype (interaction, P  < 0.05). Conversely, the apolipoprotein ε4 genotype and higher vitamin B12 intake both attenuated the inverse association between Hcy and cognition across several domains of cognitive performance (interaction, P  < 0.05). Conclusions: The relationship between cognitive performance and one-carbon metabolites, notably glycine and homocysteine, is modified by vitamin B12 intake, apolipoprotein E genotype, and status of inter-connected metabolites. These findings point towards the need for a personalized approach to dietary interventions which protect against age-related cognitive decline. Funding Sources: This work was supported by the Health Research Council of New Zealand and AgResearch Ltd.